2020
DOI: 10.1364/osac.393842
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-optical dynamics of a nonlinear GaInP photonic crystal nanocavity depend on the optical mode profile

Abstract: We measure the dynamics of the thermo-optical nonlinearity of both a mode-gap nanocavity and a delocalized mode in a Ga0.51In0.49P photonic crystal membrane. We model these results in terms of heat transport and thermo-optical response in the material. By step-modulating the optical input power we push the nonlinear resonance to jump between stable branches of its response curve, causing bistable switching. An overshoot of the intensity followed by a relaxation tail is observed upon bistable switching. In this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This probe absorption is the origin of the TO nonlinearity which causes the wellknown hysteresis behavior shown in Fig. 2(b) [30,34]. Secondly, Fig.…”
Section: Experiments and Theorymentioning
confidence: 82%
See 1 more Smart Citation
“…This probe absorption is the origin of the TO nonlinearity which causes the wellknown hysteresis behavior shown in Fig. 2(b) [30,34]. Secondly, Fig.…”
Section: Experiments and Theorymentioning
confidence: 82%
“…A pump beam is used to locally heat the PhC, and the resulting thermal change in refractive index leads to a shift in resonance frequency. Previously, our group has shown that with local thermal tuning the mode profile of a high-Q cavity can be recovered with a resolution that is limited by thermal diffusion [28][29][30]. The effective spot size depends on the surrounding medium and it is generally much larger than the optical pump spot, so that even after deconvolution a moderate resolution remains [31].…”
Section: Introductionmentioning
confidence: 99%
“…This probe absorption is the origin of the TO nonlinearity which causes the well-known hysteresis behavior shown in Fig. 2(b) [31,36]. Figures 2(c) and 2(d) show how direct heating by the pump causes a redshift of the cold cavity resonance λ 0 when the thermal profile overlaps with the optical mode profile of the resonance [29].…”
Section: Experiments and Theorymentioning
confidence: 83%
“…A pump beam is used to locally heat the PhC, and the resulting thermal change in refractive index leads to a shift in resonance frequency. Previously, our group has shown that with local thermal tuning the mode profile of a high-Q cavity can be recovered with a resolution that is limited by thermal diffusion [29][30][31]. The effective spot size depends on the surrounding medium and is generally much larger than the optical pump spot, so that even after deconvolution a moderate resolution remains [32].…”
Section: Introductionmentioning
confidence: 99%